Peningkatan Hasil Belajar Siswa dengan Model STAD Berbantuan Media Tangga Pintar pada Siswa Kelas II SD 2 Singocandi - Khoirina, Faza Nuril Ulya; Masfuah, Siti; Nilamsari, Tianida (ARZUSIN, 2025)
This study was conducted to address the problem of low student achievement in mathematics, which is attributed to the lack of appropriate instructional models and media. As a solution, the Student Teams Achievement Division (STAD) cooperative learning model was employed, combined with the use of a "smart ladder" media within a Classroom Action Research (CAR) approach. The main objective of this study was to determine the improvement in students’ mathematics learning outcomes before and after the implementation of the STAD model and smart ladder media. The study was conducted in two cycles. Data analysis results showed an improvement at each stage. In the pre-cycle phase, the students' average score was only 51.7. After implementing the first cycle, the average score increased to 65.8, although it had not yet met the minimum mastery criteria. Therefore, the study continued to the second cycle, which resulted in a significant improvement, with an average score of 80.4 and a 12% increase in mastery compared to the previous cycle. This achievement met the established mastery criteria, and the study was concluded at the second cycle. The conclusion of this study is that the application of the STAD model combined with the smart ladder media is proven to be effective in improving students’ mathematics learning outcomes. This approach is recommended as an alternative strategy for teaching mathematics in elementary schools.